Pengembangan Media Pembelajaran Digital Ular Tangga pada Materi Cerita Rakyat untuk Siswa Kelas IV SD Negeri 176 Palembang - Sendy Apria Sari; Maharani Oktavia; Hermansyah Hermansyah (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to develop a digital learning media snakes and ladders on folklore material for fourth-grade elementary school students and to determine the level of validity, practicality, and effectiveness of the developed media. This study uses the Research and Development (R&D) method with the ADDIE development model consisting of five stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research subjects were fourth-grade students of SD Negeri 176 Palembang. Data collection techniques used observation, interviews, expert validation questionnaires, student response questionnaires, and learning outcome tests. Validation was carried out by three validators consisting of material experts, media experts, and language experts. The validation results showed that the digital learning media snakes and ladders obtained an average score of 96.66% with the category of